2023
DOI: 10.1111/risa.14159
|View full text |Cite
|
Sign up to set email alerts
|

Worst‐case scenarios: Modeling uncontrolled type 2 polio transmission

Abstract: In May 2016, the Global Polio Eradication Initiative (GPEI) coordinated the cessation of all use of type 2 oral poliovirus vaccine (OPV2), except for emergency outbreak response. Since then, paralytic polio cases caused by type 2 vaccine‐derived polioviruses now exceed 3,000 cases reported by 39 countries. In 2022 (as of April 25, 2023), 20 countries reported detection of cases and nine other countries reported environmental surveillance detection, but no reported cases. Recent development of a genetically mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This section begins with a brief overview of each of the 102 studies identified by the search process summarized in Figure 1 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This section begins with a brief overview of each of the 102 studies identified by the search process summarized in Figure 1 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ,…”
Section: Resultsmentioning
confidence: 99%
“…With ongoing discussions about potential global coordination of bOPV cessation, KRI also applied its global integrated model to characterize the expected outcomes of coordinated global cessation of bOPV use in 2027 without bOPV pSIAs [ 41 ], as suggested by the 2022–2026 strategic plan [ 176 ]. In addition to exploring the expected annual paralytic cases by type over time, KRI also explored the worst-case scenarios [ 42 ]. In the context of low expectations of successful bOPV cessation, a related health economic analysis anticipated a relatively low value of antiviral drugs [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 This rapid increase in paralytic cases occurs due to the high transmissibility and neurovirulence of type 1 polioviruses, with the expected value increased by worst case iterations in which transmission occurs in countries with high transmission potential and/or low coverage. 57 Although countries and the GPEI could potentially manage bOPV cessation to minimize and potentially eliminate the risks of cVDPV1 cases, 58 , 59 current GPEI plans appear poised to repeat the experience of insufficient population immunity to transmission prior to OPV cessation that occurred with OPV2 cessation. 37 Table 2 summarizes the results from the 100 iterations for the number of iVDPV introductions by type, with 53 total expected iVDPV introductions on average for the 100 iterations the No PAVD scenario, and Table 3 summarizes the results for the numbers of cases by type, with 162 total expected cases on average for the 100 iterations of the No PAVD scenario.…”
Section: Resultsmentioning
confidence: 99%